Impact of COVID-19 on physical activity, sedentary behavior, and general health status in adults and older adults: a retrospective observational study - Alcivandro de Sousa Oliveira; Euripedes Barsanulfo Gonçalves Gomide; Lisa Fernanda Mazzonetto; Gianna Fiori Marchiori; Jéssica Fernanda Correa Cordeiro; Márcio Fernando Tasinafo-Júnior; Leonardo Santos Lopes da Silva; Pedro Pugliesi Abdalla; Ana Cláudia Rossini Venturini; Camila de Moraes; Jorge Mota; Dalmo Roberto Lopes Machado; et al. (Motricidade)
The present study aimed to compare physical activity, sedentary behavior, and general health status pre-diagnosis and post-recovery in individuals diagnosed with COVID-19; to assess the influence of COVID-19 signals, symptoms, and clinical outcomes on physical activity, sedentary behavior, and general health status in adults and older adults. A total of 509 individuals (≥ 18 years) diagnosed with COVID-19 between March 2020 and February 2021 in Ribeirão Preto/SP were evaluated. The short version of the International Physical Activity Questionnaire was used to assess physical activity and sedentary behavior, and the “profile of people diagnosed with COVID-19” questionnaire was used to self-report general health status. Data were collected via telephone regarding the week before the COVID-19 diagnosis (pre-diagnosis) and during the interview (post-recovery). There was a significant reduction in physical activity in adults and older adults (p < .001) post-recovery. Sedentary behavior increased in adults (p = .021). General health status worsened in both adults and older adults (p < .001). Symptoms such as runny nose, sore throat, and muscle pain affected physical activity; respiratory difficulty and the need for oxygen support negatively influenced sedentary behavior. Sore throat, fatigue/tiredness, and muscle pain affected general health status in adults and older adults. COVID-19 signals and symptoms negatively influenced physical activity, sedentary behavior, and general health status.